Knowledge and Attitude of Farmers towards Soil Testing Practices in Rainfed Area (Indian Journal of Extension Education, 2012)
Soil fertility and balanced use of fertilizer by the farmers is one of the important factors that determines the productivity and profitability of crop in rainfed agriculture. Soil testing is a comprehensive soil fertility evaluation programme which helps the farmers for injudicious application of chemical fertilizers. The farmers will be able to know how much nutrients are already available in the soil and how much will have to be provided additionally for a particular crop under rainfed condition. The majority of the farmers had knowledge about soil testing practices, majority of respondents were using the knowledge gained from scientists working in the Krishi Vigyan Kendra, Jaora (Ratlam) in the operational area and the personnel of State Department of Agriculture. Most of the respondents were disagree with the statements and mostly adaptors possessed unfavourable attitude towards soil testing practices. Majority of farmers agreed with statements ’Soil testing is necessary for better crop Production in rainfed area’. The efforts should be made by Krishi Vigyan Kendra (KVK) and department of agriculture to encourage the farmers in adoption of soil testing practices by organizing training programme and campaign specially on soil testing process.